2015
DOI: 10.1007/s00464-015-4395-3
|View full text |Cite
|
Sign up to set email alerts
|

Enterotomy closure using knotless and barbed suture in laparoscopic upper gastrointestinal surgeries

Abstract: Barbed closure sutures appear to be safe and effective in laparoscopic upper gastrointestinal procedures for closing enterotomies provided appropriate technique is used. The potential benefit is simplifying intracorporeal enterotomy closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Another systematic review concluded that compared with the use of conventional suture, the total operative time of laparoscopic myomectomy (SMD −0.58; 95% CI, −0.88 to −0.28) and the suturing time to close the uterine incision (SMD −1.38; 95% CI, −1.86 to −0.90) were significantly reduced with the use of barbed sutures. In addition to a reduction in operative time at gynecological surgeries, there are emerging data on other benefits and their successful application to minimally invasive urological and gastrointestinal surgeries 15‐19 . The results of cosmesis after dermal closure with barbed sutures during cesarean were documented as non‐inferior to the conventional sutures in the one trial that was included 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review concluded that compared with the use of conventional suture, the total operative time of laparoscopic myomectomy (SMD −0.58; 95% CI, −0.88 to −0.28) and the suturing time to close the uterine incision (SMD −1.38; 95% CI, −1.86 to −0.90) were significantly reduced with the use of barbed sutures. In addition to a reduction in operative time at gynecological surgeries, there are emerging data on other benefits and their successful application to minimally invasive urological and gastrointestinal surgeries 15‐19 . The results of cosmesis after dermal closure with barbed sutures during cesarean were documented as non‐inferior to the conventional sutures in the one trial that was included 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a reduction in operative time at gynecological surgeries, there are emerging data on other benefits and their successful application to minimally invasive urological and gastrointestinal surgeries. [15][16][17][18][19] The results of cosmesis after dermal closure with barbed sutures during cesarean were documented as non-inferior to the conventional sutures in the one trial that was included. 12 Comparable cosmetic outcomes have been documented with their use for dermal closure in benign gynecological surgeries; however, the patient satisfaction rate with the use of barbed sutures was significantly higher than with staples (70.12 ± 20.93 vs 50.56 ± 17.46, P < .001).…”
Section: Countrymentioning
confidence: 99%
“…Recently, several studies are focused on barbed sutures to close gastrointestinal anastomosis after gastrectomy for cancer [39, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Bautista et al . [39], when performing barbed suture after RYGB, or Billroth II anastomosis after subtotal gastrectomies for malignancy in 50 patients, encountered one anastomotic leakage and no bleedings or stenosis. The authors concluded that intracorporeal enterotomy closure with barbed sutures is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel injury is the third most common injury in patients who sustain blunt abdominal trauma, and accounts for 50% of injuries in patients with penetrating abdominal trauma (Barnett, Love, Sepulveda, & Cheadle, 2014; Hackam, Ali, & Jastaniah, 2000; Virmani, George, MacDonald, & Sheikh, 2013). Management of these injuries typically involves at least one resection of the damaged segment, often leading to further complications, in particular short bowel syndrome (SBS) and its associated nutritional deficiencies (Bautista et al, 2016; Facy et al, 2013; Guarino, Hassett, & Luchette, 1995; Wengerter, Emre, Park, & Geibel, 2016). Several conditions and disease processes can lead to SBS, which is characterized by metabolic and nutritional derangements as a result of lack of adequate length of functional small intestine.…”
Section: Introductionmentioning
confidence: 99%